Inovasi UMKM Boga Tradisional Dalam Mencapai Keunggulan Bersaing - Laili Savitri Noor; Derriawan; Soebagyo (JRB-Jurnal Riset Bisnis, 2018)
Empowerment of Small and Medium Enterprises (SMEs) becomes very strategic, because of its huge potential in driving the economic activities of the community and at the same time being the foundation of the income sources of some people in improving their welfare. But there are still many problems faced by Indonesian SMEs, some of which include competitiveness of MSMEs in national and global markets. The low competitiveness of these SMEs as expressed by Kumorotomo (2008), is due to the large number of problems in the development of MSMEs, such as financing, marketing, management and development of Human Resources (HR), and production efficiency and innovation. Where organizations that have advantages can be pursued through product and service innovation. The specific objective in this study is to produce an innovation model for MSMEs that produce traditional regional food products, so that they can help them find strategies to win the competition. This SMEs innovation model is carried out through innovation so that it can have an influence on improving the competitiveness of SMEs, especially traditional food producers in Jakarta.